2014
DOI: 10.1007/s11010-014-2021-7
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen improves the proliferation and differentiation of hBMSCs derived from postmenopausal osteoporosis through notch signaling pathway

Abstract: Estrogen deficiency is the main reason of bone loss, leading to postmenopausal osteoporosis, and estrogen replacement therapy (ERT) has been demonstrated to protect bone loss efficiently. Notch signaling controls proliferation and differentiation of bone marrow-derived mesenchymal stem cells (BMSCs). Moreover, imperfect estrogen-responsive elements (EREs) were found in the 5′-untranslated region of Notch1 and Jagged1. Thus, we examined the molecular and biological links between estrogen and the Notch signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 25 publications
(32 reference statements)
2
47
0
Order By: Relevance
“…Studies have highlighted a correlation between the Notch signaling pathway and Haju-Cheney syndrome, a disorder that results in osteoporosis [12]. The proliferation and differentiation of bone cells from osteoporotic patients could be increased due to an enhanced Notch signaling pathway; thus, that pathway deserves to be a potential target for osteoporosis treatment [13]. Delta-like 3 (DLL3), which at present has only been identified in mammals, is a divergent ligand and modulator located in the Notch signaling pathway, with variations in its expression linked to osteogenic induction [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have highlighted a correlation between the Notch signaling pathway and Haju-Cheney syndrome, a disorder that results in osteoporosis [12]. The proliferation and differentiation of bone cells from osteoporotic patients could be increased due to an enhanced Notch signaling pathway; thus, that pathway deserves to be a potential target for osteoporosis treatment [13]. Delta-like 3 (DLL3), which at present has only been identified in mammals, is a divergent ligand and modulator located in the Notch signaling pathway, with variations in its expression linked to osteogenic induction [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few gene targets have been rigorously validated by reporter assays and these are shown in Table 2. Overall, mir363-3p appears to targets genes directly or indirectly involved with apoptotic cell death (Li et al, 2016, Wang et al, 2016), and some of these genes display either functional sex differences or are responsive to estrogen (Tsukahara et al, 2006, Tsukahara, 2009, Utge et al, 2010, Sharma et al, 2011, Caliceti et al, 2013, Fan et al, 2014, Zhao et al, 2014, Shannonhouse et al, 2015). Both caspase-3 and -9 play a role in apoptotic cell death, with caspase-9 being an initiator caspase, and caspase-3, an executioner caspase.…”
Section: Resultsmentioning
confidence: 99%
“…22 Notch signaling is increasingly recognized as a crucial participant in human skeletal development and homeostasis. Notch regulates chondrocytic and osteogenic differentiation, and dysregulation of Notch signaling may lead to a series of skeletal disorders such as osteosclerosis, 23 osteoporosis, 24 chondrodysplasia, 25 osteoarthritis, 26 osteosarcoma, 27 and congenital diseases or syndromes. 28 The present study confirmed that Notch receptor Notch2, Notch ligand JAG1, and target gene HES1 were up-regulated in OLF cells.…”
Section: Discussionmentioning
confidence: 99%